The Essenes, the scrolls, and the Dead Sea - Taylor, Joan E. (Oxford University Press, 2013)
The mystery surrounding the Dead Sea Scrolls remains, over 60 years after their rediscovery. Who hid them and why? This book reinvigorates the contested hypothesis that the Essenes were responsible. Rather than being a marginal esoteric sect, Taylor shows that this group acted as one of the leading legal schools of Judaism